A randomized controlled trial of a brief versus standard group parenting program for toddler aggression. Issue 3 (17th November 2016) - Tully, Lucy A.; Hunt, Caroline
Abstract : Physical aggression (PA) in the toddler years is common and developmentally normal, however, longitudinal research shows that frequent PA is highly stable and associated with long‐term negative outcomes. Significant research has demonstrated the efficacy of parenting interventions for reducing externalizing behavior in children yet their typical length may overburden families, leading to low participation rates and high attrition rates. To increase the reach of parenting interventions and impact on the prevalence of externalizing behavior problems, brief interventions are needed. This RCT compared a standard (8 session) group Triple P to a brief (3 session) discussion group and a waitlist control for reducing toddler PA, dysfunctional parenting and related aspects of parent functioning. Sixty‐nine self‐referred families of toddlers with PA were randomized to the respective conditions. At post‐assessment, families in the standard intervention had significantly lower levels of observed child aversive behavior, mother reports of PA and dysfunctional parenting, and higher levels of mother‐ and partner‐rated behavioral self‐efficacy than the waitlist control. Families in the standard intervention also had significantly lower levels mother‐rated dysfunctional parenting than the brief intervention, and the brief intervention had significantly lower levels of mother‐rated dysfunctional parenting than waitlist. There were no significant group differences at post‐assessment for measures of parental negative affect or satisfaction with the partner relationship. By 6 month follow‐up, families in the brief and standard intervention did not differ significantly on any measure. The implications of the findings to delivery of brief parenting interventions are discussed. Aggr. Behav. 43:291–303, 2017. © 2016 Wiley Periodicals, Inc.